Waste to valuable by product - utilization of carbonised decanter cake from palm oil milling plant as an effective adsorbent for heavy metal ions in aqueous solution - Nugroho , Dewayanto (2010)
Palm oil milling plant generates large amount of waste that was proven to cause environmental problems. About 40 kg decanter cake was generated from each ton of fresh fruit bunch processed. Previous studies suggested agricultural waste could be employed as heavy metal ion adsorbent. Due to the similarity of decanter cake with other agricultural waste we proposed to explore the use of decanter cake as an adsorbent for heavy metal ion removal. Utilization of decanter cake as an effective adsorbent for Cd 2 , Cu2 and Pb2 ion removal from aqueous solution has been studied. The decanter cake was first dried at 105 °C and then carbonized at various temperatures. The resulting carbonized decanter cake were tested for removing Cd2 , Cu 7+ and Pb2 ions. Proximate analysis using thermogravimetry analysis of decanter cake carbonized at 500 °C indicated that the adsorbent contained 4% moisture, 21% volatile,23% fixed carbon, and 52% ash. Adsorption test were normally carried out by mixing 1.0 g of the decanter cake in 100 mL aqueous solution of the various ions. The concentration of metal ions in the solutions used is in the range of 100 - 1000 mg/t. The results of adsorption studies indicated that the removal of metal ions was highest in the case of Pb2 when the carbonization temperature was 500 °C and 600 °C in the case of Cd2 and Cu2 . Maximum removal of the Cd2 , Cu2 and Pb2 were also observed to take place when the pH of the solution is in the range of 4 - 5. Langmuir and Freundlich isotherm models were used to fit the isotherm experimental data. The maximum uptakes of Cd2 , Cu2 and Pb2 onto the carbonized decanter cake in this study were estimated to be 24, 23, and 97 mg/g respectively. Adsorbed metal ions can be desorbed from adsorbent using dilute HC1 solution. The adsorption kinetics was found to follow the pseudo-second-order kinetic model. Thermodynamic parameters such as standard enthalpy (MI"), standard entropy (AS-) and Gibbs free energy (AG-) were determined. Adsorption process was endothermic and had negative value of Gibbs free energy changes. The competitive adsorption characteristics of binary and ternary heavy metal ions Cd2 , Cu2 and Pb2 on PDC500 were investigated in batch systems. Equilibrium adsorption data showed that PDC500 displays a high selectivity toward one metal in two-component or a three-component system with an affinity order of Pb2> Cu2 > Cd2 Chemical activation of decanter cake using ZnC12 increased the maximum adsorption capacity for Cd2 , Cu2 and Pb2 significantly to 52, 44, and 159 mg/g respectively. Kinetic and thermodynamic properties of adsorption were affected by chemical activation. Scale up of the batch process into industrial scale was explored using the Langmuir parameter from experimental data. A three-stage continuous counter current adsorption unit gave the best adsorption performance for Pb2 ion removal in term of minimum adsorbent consumption.